TİROİD VE KARACİĞER - ÖZDEMİR, Sebati (Cerrahpaşa Medical Journal, 2014)
Background.- The liver has an important role in the metabolism of thyroid hormones. Therefore, thyroid functions may be affected by liver diseases. Especially, autoimmune thyroid manifestations can develop during hepatitis C virus infection, and interferon therapy can induce thyroid dysfunctions. Conversely, thyroid diseases may cause alterations in liver morphology and functions. Moreover, hepatotoxicity can evolve during antithyroid therapy. In this paper relationships between thyroid and liver were reviewed.